Investigation and evaluation of ultrasound reactor for reduction of fungi from sewage - Dehghani, Mohammad Hadi (Zhejiang University Press, 2007)

(untitled)
The objective of the investigation was to study the application of ultrasound reactor technology (USRT) as a disinfectant for reduction of fungi from sewage effluent. Fungi are carbon heterotrophs that require preformed organic compounds as carbon sources. USRT is an attractive means to improve water quality because of the system simplicity and no production of toxic by-products. An ultrasound reactor produces strong cavitation in aqueous solution causing shock waves and reactive free radicals by the violent collapse of the cavitation bubble. These effects should contribute to the physical disruption of microbial structures and inactivation of organisms. There was significant reduction in fungal growth, with decreased fungal growth with increasing USRT. In this study, ultrasound irradiation at a frequency of 42 kHz was used to expose suspensions of fungi to evaluate the disinfection efficacy of the ultrasound reactor. Also, this study showed that in this system more than 99% reduction of sewage fungi was achieved after 60 min.